Serum sICAM-1 and Galectin-3 Levels in Diabetic Patients with COVID-19 - Busra Karahan; Dogan Nasir Binici; Omer Karasahin; Sibel İba Yilmaz; Ahmet Kiziltunc; Filiz Mercantepe (Viruses, 2025)
Introduction: This study aimed to evaluate the diagnostic and prognostic value of soluble intercellular adhesion molecule-1 (sICAM-1) and galectin-3 in patients with type 2 diabetes mellitus (T2D) diagnosed with coronavirus disease 2019 (COVID-19). Participants and Method: This prospective observational study included 45 adult patients (≥18 years) with T2D and confirmed COVID-19 who were followed in the Infectious Diseases and Clinical Microbiology departments between May and June 2022. The control group consisted of 45 healthy volunteers without chronic illness who were presented to the internal medicine outpatient clinic. In addition to routine laboratory biomarkers assessed at hospital admission, the serum levels of sICAM-1 and galectin-3 were measured via ELISA kits. Results: The median age of the patients was 66 years (range: 41–77), and 23 (51.1%) were male. Hypertension was the most common comorbidity in addition to diabetes. Compared with those in the control group, the serum levels of both galectin-3 and sICAM-1 were significantly elevated in patients with COVID-19 and T2D (p < 0.001). However, there was no significant difference in galectin-3 or sICAM-1 levels between survivors and nonsurvivors (p = 0.240 and p = 0.266, respectively). Conclusion: Galectin-3 and sICAM-1 demonstrated stronger diagnostic utility than conventional biomarkers in T2D patients with COVID-19. The elevated levels of these markers may reflect the underlying systemic inflammation observed in diabetic patients with COVID-19. The strong correlation between galectin-3 and sICAM-1 suggests a potential link in their inflammatory regulation, although causality cannot be inferred.